Eksistensi Keluarga dalam Mendorong Pendidikan Bagi Perempuan pada Masyarakat Pamekasan, Madura - Annisa Luluk Firdausie (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Talking about gender has certainly become a very common discussion, especially in a patriarchal country. The purpose of this study is to obtain an in-depth description of the role of the family in women's education in gender equality and social development of Muslim communities in Pamekasan. The researcher used a qualitative-narrative method with a liberal feminist analysis. Data collection techniques include interviews, observations, and documentation in Muslim communities or Muslim families in the Pamekasan area. The researcher used a qualitative-narrative method with the theory of Liberal Feminism by Mary Wollstonecraft. The results of this study show how the role of the family in shaping gender understanding is very crucial, it can be a driving force or even an incredibly dangerous obstacle. Education is certainly the basis for providing a space for open reasoning for women to live in the public sphere. In the Pamekasan community, Madura, informants found that the patriarchal culture within the family environment still holds strong, considering women as second-class citizens. Therefore, the informants faced the first challenge from their family environment in gaining access to education. The informants found that they were underestimated and disrespected as women, not just because they were born as women but also because they were disrespected because they could not do anything but were guarded like women living in a family cage.